Time-Dependent Gene Profiling Indicates the Presence of Different Phases for Ischemia/Reperfusion Injury in Retina. (January 2014) - Andreeva, Kalina; Zhang, Meixia; Fan, Wei; Li, Xiaohong; Chen, Yinlu; Rebolledo-Mendez, Jovan D.; Cooper, Nigel G.
Ischemia/reperfusion (IR) injury has been associated with several retinal pathologies, and a few genes/gene products have been linked to IR injury. However, the big picture of temporal changes, regarding the affected gene networks, pathways, and processes remains to be determined. The purpose of the present study was to investigate initial, intermediate, and later stages to characterize the etiology of IR injury in terms of the pathways affected over time. Analyses indicated that at the initial stage, 0-hour reperfusion following the ischemic period, the ischemia-associated genes were related to changes in metabolism. In contrast, at the 24-hour time point, the signature events in reperfusion injury include enhanced inflammatory and immune responses as well as cell death indicating that this would be a critical period for the development of any interventional therapeutic strategies. Genes in the signal transduction pathways, particularly transmitter receptors, are downregulated at this time. Activation of the complement system pathway clearly plays an important role in the later stages of reperfusion injury. Together, these results demonstrate that the etiology of injury related to IR is characterized by the appearance of specific patterns of gene expression at any given time point during retinal IR injury. These results indicate that evaluation of treatment strategies with respect to time is very critical.